Analysis Of The Relationship Between Compliance With Antihypertensive Drug Use And The Therapy Output Of Hypertension Patients At The Sangkrah Community Health Center In Surakarta - Rosmala Dewi; Vivin Marwiyati Rohmana; Aprilia puteri Santika (International Journal of Health Engineering and Technology, 2026)
Hypertension is a chronic disease with a high prevalence and remains a major public health problem that requires long-term therapy and optimal blood pressure control to prevent complications. Treatment success is influenced by various factors, including adherence to antihypertensive medication. Poor adherence may result in uncontrolled blood pressure and reduced therapeutic outcomes. This study aimed to analyze the relationship between adherence to antihypertensive medication use and therapeutic outcomes among hypertensive Patients at Sangkrah Primary Health Center, Surakarta. This study employed an observational analytic design with a cross-sectional approach. The study population consisted of hypertensive patients who met the inclusion criteria. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), while therapeutic outcomes were assessed based on blood pressure records documented in patients' medical files. Data were analyzed using univariate analysis to describe respondent characteristics and bivariate analysis using the chi-square test to examine the association between medication adherence and therapeutic outcomes. The results showed that most respondents were classified as adherent, with 90 respondents (90.0%), while 10 respondents (10.0%) were non-adherent. Regarding therapeutic outcomes, 74 respondents (74.0%) had uncontrolled blood pressure and 26 respondents (26.0%) had controlled blood pressure. Chi-square analysis showed a Pearson Chi-Square value of 0.208 (p > 0.05), indicating no statistically significant relationship between medication adherence and therapeutic outcomes. In conclusion, adherence to antihypertensive medication was not significantly associated with blood pressure control. These findings indicate that blood pressure management is influenced not only by medication adherence but also by factors, comorbidities, and nonpharmacological interventions.